Study of degradation of quality of soyabean biodiesel with storage time and its emissions on various loads - Kumar S.; Shukla S.K. (My University, 2025)
With many of its properties matching with that of the diesel oil and its possible applicability in the existing compression-ignition engine, biodiesel production and commercialization has gained enough popularity. The main disadvantage of biodiesel is its quality degradation with storage time which is mainly due to the rancidity that the biodiesel faces upon storage. This paper investigates on the degradation of the burning characteristics namely: - calorific value and viscosity of Soyabean methyl ester (SBME) over a storage period of 15 days; stored in polyethylene tank in a dark place. The emissions of the biodiesel blended at different proportion with the conventional diesel oil were also observed for varying load and compression ratios of the CI engine. A decreasing curve for the calorific value and an increasing curve for kinematic viscosity were observed for the SBME sample at different storage period. The carbon monoxide decreases with increase in load, while hydrocarbon almost constant in the emission. Nitrogen monoxide and carbon dioxide content increases with increase in load to a particular point of maxima and then decreases with further increase in the load. The oxygen content shows exactly the opposite behaviour with respect to carbon dioxide. © 2018 Elsevier Ltd.